Potential roles of telocytes in lung diseases. (July 2016) - Shi, Lin; Dong, Nian; Chen, Chengshui; Wang, Xiangdong
Abstract: Telocytes (TCs) are a unique type of interstitial cells with specific, extremely long prolongations named telopodes (Tps), as shown by immune-positive staining against CD34, c-kit and vimentin. They were found in many organs of mammals, with potential biological functions, including the trachea and lung, even though the exact function remains unclear. Here, we give a historical overview of the TCs research field and summarize the latest findings associated with TCs, with a special focus on the recent progress about TCs specific gene and protein profiles that has been made in understanding that TCs may play a potential, but important, role in the pathogenesis of lung diseases.